Gender Bias in Tax Systems - Stotsky, Janet (IMF Working Papers; Working Paper, 1996)
This paper examines the nature of gender bias in tax systems. Gender bias takes both explicit and implicit forms. Explicit gender bias is found in many personal income tax systems. Several countries, especially those in Western Europe, have undertaken to eliminate explicit gender bias in recent years. It is more difficult to identify implicit gender bias, since this depends in large part on value judgments as to desirable social and economic behavior. Implicit gender bias has also been a target for reform of tax systems in recent years.